2013
DOI: 10.1002/app.40075
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental–numerical rheometric and mechanical characterization of EPM/EPDM rubber for medium voltage cable applications vulcanized with peroxides

Abstract: The vulcanization of medium and high voltage (M-H V) cables is an important industrial application where manufacturers use principally EPM/EPDM, crosslinked polyethylene (XLPE) and now also thermoplastic rubbers. In the present article, an EPDM compound for medium voltage cablesnormally distributed to producers in pellets and ready to be curedis considered and several experimental tests (rheometer curves and mechanical characterizations) are conducted changing controlled curing temperature, peroxide type and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In terms of SG‐Si6490 treated mica, there are CC groups in vinyl groups in SG‐Si6490 on mica surface, which can participate into vulcanization process, and generate extra chemical crosslinks. So the chemical crosslinks of EPDM increases . In this way, the M H and cure rate of EPDM/BaTiO 3 /SG‐Si6490 composites increases simultaneously …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In terms of SG‐Si6490 treated mica, there are CC groups in vinyl groups in SG‐Si6490 on mica surface, which can participate into vulcanization process, and generate extra chemical crosslinks. So the chemical crosslinks of EPDM increases . In this way, the M H and cure rate of EPDM/BaTiO 3 /SG‐Si6490 composites increases simultaneously …”
Section: Resultsmentioning
confidence: 90%
“…Researchers reported that coupling agents of various type can not only reduce the agglomeration of fillers in rubber, but also can retard or promote the vulcanization of rubbers . However, there were no reports about the combined usage of coupling agents on the properties of EPDM/BaTiO 3 /mica composites.…”
Section: Introductionmentioning
confidence: 99%